1999
DOI: 10.1038/6165
|View full text |Cite
|
Sign up to set email alerts
|

Conditional expression and signaling of a specifically designed Gi-coupled receptor in transgenic mice

Abstract: To control G protein signaling in vivo, we have modified G protein-coupled receptors to respond exclusively to synthetic small molecule agonists and not to their natural agonist(s). These engineered receptors are designated RASSLs (receptor activated solely by a synthetic ligand). A prototype RASSL (Ro1) based on the Gi-coupled K opioid receptor was expressed in transgenic mice under the control of the tetracycline transactivator (tet) system. Activation of Ro1 expressed in the heart decreased heart rate by up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(156 citation statements)
references
References 23 publications
3
152
0
Order By: Relevance
“…Although immunostaining of the aortae for HA in the binary transgenic mice was unsuccessful, suggesting a low level of expression, we were able to detect RVCH-HA in aortic tissue by immunoprecipitation, starting with a relatively large sample (10 aortae). These results are comparable, however, to those recently obtained in studies in which Tet-Off was used successfully to express another transgene in a target organ (25). Despite a relatively low level of expression, we were able to show that a phenotype could be produced when a gene of interest was conditionally expressed in vascular SMC.…”
Section: Discussionsupporting
confidence: 59%
“…Although immunostaining of the aortae for HA in the binary transgenic mice was unsuccessful, suggesting a low level of expression, we were able to detect RVCH-HA in aortic tissue by immunoprecipitation, starting with a relatively large sample (10 aortae). These results are comparable, however, to those recently obtained in studies in which Tet-Off was used successfully to express another transgene in a target organ (25). Despite a relatively low level of expression, we were able to show that a phenotype could be produced when a gene of interest was conditionally expressed in vascular SMC.…”
Section: Discussionsupporting
confidence: 59%
“…We first generated Tie2-tTA mice in which the tTA is expressed in ECs by the Tie2 promoter and enhancer (18). To assess transgene expression in adult mice, we performed a reporter assay with mice carrying LacZ under the control of the TRE (23). To achieve adult expression in this experiment and all others, doxycycline (Dox), a more stable derivative of tetracycline, was administered throughout the gestation period until weaning (3 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Transgene expression was activated by switching the mice to regular mouse chow without doxycycline at 4 weeks of age (LabDiet 5053; PMI Nutrition). Full transgene expression was expected to occur within 2 weeks after doxycycline withdrawal, based on prior data (20). qPCR from whole femurs of 6-week-old adult mice showed that Rs1 expression was induced Ϸ4-to 80-fold above that of age-matched ColI(2.3)ϩ/Rs1ϩ mice that were chronically maintained on doxycycline (SI Fig.…”
Section: Generation Of Micementioning
confidence: 99%
“…RASSLs are engineered receptors that no longer respond to endogenous hormones but can be activated by synthetic smallmolecule drugs. They have proven useful for studying the roles of activated G protein signaling (18)(19)(20) and basal G protein activity (21,22) in complex systems, including cardiomyocyte and neurological development and function.…”
mentioning
confidence: 99%